Bacterial Etiology, Antibiotic Sensitivity Pattern and Risk Factors for Asymptomatic Bacteriuria during Pregnancy: Experience in a Tertiary Care Hospital - Khanum, Shakila; Ahmed, Jamal Uddin; Khanam, Khaleda (BIRDEM Medical Journal, 2017)
Background: Urinary tract infections (UTIs) are common during pregnancy. Untreated asymptomatic bacteriuria (ASB) during pregnancy may cause serious complications including pyelonephritis and delivery of premature or low-birth-weight infants. This study aimed to assess the risk factors for asymptomatic bacteriuria, bacterial agents and their antibiotic susceptibility pattern in pregnant women attending in Combined Military Hospital (CMH), Dhaka. Methods: This cross-sectional study was conducted in a total of 1540 pregnant women with no signs and symptoms of UTI from October 2013 to March 2015. Clean catch mid-stream urine samples were collected from all study participants using sterile containers. Urine samples were cultured using standard bacteriological methods. Identification of suspected colonies and antibiotic sensitivity testing were done. Patients having ASB were further evaluated to find out associated risk factors. Results: Out of 1540 pregnant women, 254 (16.5%) had asymptomatic bacteriuria (Colony forming unit >105/mL).The most frequently isolated bacteria were Escherichia coli (E. coli) (50.4%), followed by Klebsiella (24.0%). The antibiotic sensitivity rate of bacterial isolates were highest for imipenem and amikacin. Among different associated conditions, anemia (16.5%), gestational diabetes mellitus (GDM) (10%) and past history of UTI (5.1%) were found to be the most frequent factors associated with increased prevalence of ASB. Conclusion: In this study, the prevalence of ASB was high among pregnant women with anemia, GDM and past history of UTI. E. coli was the most common organism causing ASB, which is less susceptible to conventional oral antibiotics but more susceptible to imipenem and amikacin. So, careful drug selection is required for successful outcome in ASB. Birdem Med J 2016; 6(2): 79-83